1999
DOI: 10.1007/s001340051012
|View full text |Cite
|
Sign up to set email alerts
|

TISS and mortality after discharge from intensive care

Abstract: In a hospital without HDU facilities, patients who are receiving HDU levels of care on discharge from the ICU have a high in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 28 publications
1
36
0
7
Order By: Relevance
“…Recently Smith et al [7] analyzed 238 patients discharged alive from the ICU to in-hospital wards. They found that high Therapeutic Intervention Scoring System (TISS) [15] levels on discharge from the ICU were associated with an increased risk of in-hospital mortality, with mortality rates ranging from 7.3 % in patients with a predischarge TISS lower than 10, to 21.4 % in those with a predischarge TISS greater than 19.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Smith et al [7] analyzed 238 patients discharged alive from the ICU to in-hospital wards. They found that high Therapeutic Intervention Scoring System (TISS) [15] levels on discharge from the ICU were associated with an increased risk of in-hospital mortality, with mortality rates ranging from 7.3 % in patients with a predischarge TISS lower than 10, to 21.4 % in those with a predischarge TISS greater than 19.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are hardly any systematic studies of how daily severity of illness score changes from admission to initial discharge predict ICU readmission [32,52] . Besides the severity of illness score, there is also an association between nursing workload and post-ICU mortality [65,66] . The Therapeutic Intervention Scoring System (TISS) has been widely applied to assess workload and resource allocation in intensive care, measuring treatment intensity [67][68][69] .…”
Section: Readmission?mentioning
confidence: 99%
“…Consequently, attempts have been made to use TISS scores to categorize the level of care that patients require and even to evaluate the care required after ICU discharge [1,68] . Several authors have shown an association of the TISS value of the last ICU day with post-ICU mortality [65,66,69,70] and therefore indirectly the association with ICU readmission. Smith et al [66] concluded in their research that the mean TISS scores in patients readmitted to the ICU were significantly higher than in patients who did not require readmission [65,66] .…”
Section: Readmission?mentioning
confidence: 99%
See 1 more Smart Citation
“…Quality of care differences and higher order interactions within ICUs are not captured in simple regression statistical models. For example, quality issues such as night-time discharges [17] and level of support prior to discharge [18] have been shown to affect outcome. Such differences influence hospital mortality, and if not included in the prediction model tend to degrade its performance.…”
Section: Discriminationmentioning
confidence: 99%